Intervention of Finger Hold Relaxation Technique on Reduction of Pain Scale in Cholelithiasis Patients After Cholecystectomy Surgery - Nurhasanah, Ina; Rahman, Irpan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Background: Cholelithiasis, or what is known as gallstones, is a condition that often occurs in the gallbladder. This disease is more often found in individuals with obesity, diabetes mellitus, and high cholesterol levels. In Indonesia, around 1 million patients are diagnosed with cholelithiasis every year, and around two-thirds of them require surgery. Post-surgery, pain is a common complaint experienced by patients. Pain management can be done through pharmacological and non-pharmacological therapy. One effective non-pharmacological therapy is the finger hold relaxation technique or finger grip therapy. This technique provides benefits to the body, mind, and soul, so it can help reduce pain through the relaxation process. Objective: To determine the effect of the finger hold relaxation technique on reducing pain in post-cholecystectomy patients. Method: Using the case study method where the researcher manages 1 case. Research Results: After using the finger hold relaxation technique, the patient reported a decrease in the pain scale from scale 7 to scale 1. This reduction was achieved within three days with the support of administering analgesic drugs. Conclusion: The finger hold relaxation technique reduces the pain scale in post-cholecystectomy patients.